Evaluating the effect of nano-particle additives in Kevlar® 29 impact resistant composites. (8th September 2015) - Manero, Albert; Gibson, Jason; Freihofer, Gregory; Gou, Jihua; Raghavan, Seetha
Abstract: Kevlar® 29 impact resistant composites are commonly employed for a wide range of applications including ballistic resistant armor. Advancement in the composite's energy absorption and the reduction of weight are critical for increasing their effectiveness in application. Carbon nano-tubes and nano-sized core shell rubber particles are added for thermoset resin systems to enhance toughness and energy absorption. V 50 ballistic testing was conducted on three classes of Kevlar composites and their energy absorption characteristics were evaluated with a ballistic impact testing and post shot Raman spectroscopy. This study showcases the influence of nano-particle additives on the energy absorption of the composite via the Kevlar® 29 fibers corresponding residual Raman spectral shifts. Investigating both the 1611 cm −1 and the 1649 cm −1 reference Raman bands, a discussion of as to how the additives are enhancing energy absorption and overall composite performance is presented as well. This work indicates that different mechanisms employed by the two different nano-additives enhance V 50 ballistic performance by 7.3% and 8% respectively over baseline panels with a 1% weight addition of nano and micro-sized particles by matrix toughening, cavitation, and strengthening the fiber–matrix interface.